2012
DOI: 10.1242/dev.074948
|View full text |Cite
|
Sign up to set email alerts
|

Canonical BMP7 activity is required for the generation of discrete neuronal populations in the dorsal spinal cord

Abstract: SUMMARYBMP activity is essential for many steps of neural development, including the initial role in neural induction and the control of progenitor identities along the dorsal-ventral axis of the neural tube. Taking advantage of chick in ovo electroporation, we show a novel role for BMP7 at the time of neurogenesis initiation in the spinal cord. Using in vivo loss-of-function experiments, we show that BMP7 activity is required for the generation of three discrete subpopulations of dorsal interneurons: dI1-dI3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
109
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(115 citation statements)
references
References 43 publications
5
109
1
Order By: Relevance
“…The majority of BMPs have specific functions in neurogenesis, BMP-2 is crucial in gliogenesis [18, 19]. Mainly, when telencephalic neural progenitors are exposed to BMP-2, their developmental fate is switched to the astrocytic cell lineage [20, 21].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of BMPs have specific functions in neurogenesis, BMP-2 is crucial in gliogenesis [18, 19]. Mainly, when telencephalic neural progenitors are exposed to BMP-2, their developmental fate is switched to the astrocytic cell lineage [20, 21].…”
Section: Introductionmentioning
confidence: 99%
“…This signaling cascade can be blocked by the inhibitory (I) Smads, Smad6 and Smad7 (Imamura et al, 1997; Nakao et al, 1997). Previous studies examining the role of the Smads establishing neural circuitry in the chicken spinal cord have shown that Smad1, Smad5 and Smad4 are critical for pattern formation in the dorsal neural tube (Chesnutt et al, 2004; Le Dreau et al, 2012). Moreover, we recently demonstrated that the I-Smads have distinct functions spatially limiting the response of dorsal cells to BMP signaling (Hazen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, this model was proposed largely by analogy with the patterning events in the ventral spinal cord. There are many BMPs present in the roof plate (Butler and Dodd, 2003; Liem et al, 1997) and studies have also suggested that some of them have specific effects on the induction of particular neural fates (Le Dreau et al, 2012; Lee et al, 1998). An additional four classes of INs (dI4 to dI6, dIL) arise independently from signals from the roof plate; their identity may be dependent on signals from the adjacent paraxial mesoderm (Le Dreau and Marti, 2013).…”
Section: The Molecular and Cellular Organization Of Spinal Cordmentioning
confidence: 99%